Agreement, case assignment and nominal coordination - Hristov, B (2012)
The topic of this dissertation is agreement and case assignment, with particular reference to conjoined noun phrases. The initial chapters look at the different possibilities available in such contexts, including agreement with the features of each individual conjunct, agreement with the features of only one conjunct, or agreement with features computed on the basis of those of the individual conjuncts but not necessarily possessed by them. We propose a way of handling all of these patterns with a single formal mechanism, later applying the same intuitions to the assignment (or non-assignment) of case values by a head to its dependents. Attempts are also made to explore in greater depth some of the factors that might influence the choice of alternative agreement configurations, as well as to extend the scope of the model which we elaborate as we go along to non-conjoined environments where variable agreement occurs. Special emphasis is laid throughout on fluctuations in agreement, either because the controller has mismatched attributes or because the syntactic structure and/or the semantic interpretation allow variation. The final conclusion is that a modular approach to grammar is best placed to deal with the empirical facts. The complexities of the data call for bringing together purely morpho-syntactic, declensional information, syntactic hierarchy, order and constituency, coupled with semantics and pragmatics. The successful, appropriately regulated, interaction of these modules is shown to offer a satisfactory explanation which is difficult to obtain by exclusively relying on syntax or semantics alone.